Spatial metabolomics informs the use of clinical imaging for improved detection of cribriform prostate cancer - Nikita Sushentsev; Gregory Hamm; Roido Manavaki; Mary A. McLean; Jonathan Birchall; Dmitry Soloviev; David Y. Lewis; Luigi Aloj; Lucy Flint; Aleksandr Zakirov; Ian G. Mills; Vincent J. Gnanapragasam; et al. (Proceedings of the National Academy of Sciences, 2025)
Cribriform prostate cancer (crPCa) is associated with poor clinical outcomes, yet its accurate detection remains challenging due to the poor sensitivity of standard-of-care diagnostic tools. Here, we use untargeted spatial metabolomics to identify fatty acid biosynthesis as a key metabolic pathway enriched in crPCa epithelium. We also show that imaging tumor lipid metabolism using [1- 11 C]acetate PET/CT and proton magnetic resonance spectroscopy differentiates cribriform from noncribriform intermediate-risk prostate cancers in two prospective patient cohorts. These findings support the feasibility of using clinical metabolic imaging techniques as adjunctive tools for improving crPCa detection in clinical practice, with prospective studies in larger cohorts warranted to obtain definitive results.